New Application of Piezoelectric Ultrasounds in Maxillo-facial bone surgery - Piersanti, Luigi <1973> (Alma Mater Studiorum - Università di Bologna, 2015)

(untitled)
Background: Piezoelectric instrumentation seems to offer 3 important advantages for cutting bone structures. Be more precise because it is produced by micro-vibrations from the cutting insert. Be safer because the ultrasonic frequency used does not affect soft tissue. Thirdly, the less invasive cutting action produces minor tissue damage and consequently probably a better healing Aim of the Study: The aim of this study is to evaluate the effectiveness of piezoelectric device capability in maxillo-facial surgery, in order to take advantage of these favourable capacity. Material and Methods: Considering the several potential application of the piezoelectric technology in Orthognathic, Oncologic and Extractive surgery, we would like to design protocols in order to verify how this new device can modify the surgical technique, the surgical time, the patients healing and its quality of life. Results: Due to the precise Piezosurgery cut, we can manage the Cad-Cam-Custom Made plates protocol in Oncologic Surgery and in Orthognatic Surgery increasing our percentage of comparison between the 3D preoperative plan and the surgical execution. We also found a better quality of life impaction in Patient who underwent and extractive surgery Conclusion: Piezosurgery device seems to be a strong surgical aid were safe and precise cut are needed and its capability to reduce the discomfort Patients need to be study in deep also in major surgery like Orthognatic and Oncologic surgery.